Finance Sustainability to the Environmental Investment - Alvira, Alvira; Lindrianasari, Lindrianasari; Asmaranti, Yuztitya; Oktavia, Reni (Fakultas Pendidikan Ekonomi dan Bisnis, 2020)
The aim of this research is to find the correlation between financial performance, firm size, foreign ownership as independent variables and environmental investment as dependent variable. The measurement of environmental investment is environmental investment total per assets total. This research is using quantitative approach that examined the correlation between variables through hypothesis testing. The sample of this research is 46 public listed mining companies in the period of 2014-2018 by purposive sampling method. The data and hypothesis analysis used correlation analysis.Â The results indicated that financial performance have positive correlation on environmental investment whereas firm size and foreign ownership do not have any correlation on environmental investment. Great environmental investment can lead to higher profit, reputation and legitimacy of the company.